THE ESSENCE OF THE VALUE COURAGE OF THE BUGINESE-MAKASSARESE MAN IN THE NOVEL PULAU BY ASPAR PATURUSI: A GENETIC STRUCTURAL REVIEW - Syarifuddin Tundreng; Noermanzah Noermanzah; Agus Rofi'i; Musayyedah Musayyedah (English Review: Journal of English Education, 2022)
A novel is present as an effort to tell readers about the cultural values of a particular society. Likewise, the novel Pulau by Aspar Paturusi tells the values of the courage of the Buginese-Makassarese man. Therefore, the purpose of this study is to gain an in-depth understanding of the values of the courage of Bugis-Makassar men in Aspar Paturusi's Pulau novel wholly and entirely. This research uses a qualitative approach with a content analysis method. Data were collected through repeated and in-depth reading of the novel. Furthermore, recording, coding, identification, and classification are carried out. The data are analyzed and interpreted through a deep understanding and abstraction of the society that is told in the novel. The research findings show that in the life of the people of the 70s, the values of courage for Buginese-Makassarese man, which is one of the values in the Buginese-Makassarese philosophy of life, are highly guarded, maintained, and upheld. For Buginese-Makassarese man, courage is identity, pride, honour, and authenticity. The implications of the results of this research are expected to be continuously embedded in the current and future generations as a form of existence of a good life during life's difficulties.